Spatio-Temporal Dynamic of Land Use and Land Cover in Andit Tid Watershed, Wet Frost/Afro-Alpine Highland of Ethiopia - Ibrahim, Temima; Geremew, Bethel; Tesfay, Fikrey (Edelweiss Applied Science and Technology, 2021)
Spatial and temporal dynamics of land use/land covers (LULC) are the results of human activities and population growth. The LULC change is caused by both, natural and anthropogenic factors. The objective of this study was to detect LULC changes in Andit Tid watershed. The study has used ArcGIS 10.5 and Landsat images of 1984, 1996, 2008, and 2017 to see LULC changes of Andit Tid watershed. The result indicated that the plantation forest and cultivated land have been increased by 41.94 ha and 33.39 ha, respectively from 1984 to 2017 due to the population increase and improper agricultural activity. On the other hand, the bushland and grassland coverage has been decreased by -7.29 and -67.95 ha, between the study periods respectively. This shows the tempo-spatial dynamic conditions of LULC change in the study watershed. The change of LULC was related mainly to anthropogenic factors such rapid population growth which consequence high demand land for cultivation practices, settlement and grazing land. Thus, attention must give to increase of intensified agricultural activities that increase land productivity to satisfy the ever-increasing demand of cultivated land of high population in the study watershed. A further search on the impact of these LULC changes on the livelihood and ecosystem services is recommended.